Analysis of the Technological Maturity Cycle of Antibacterial and Self-cleaning Surfaces based on TiO2/ZnO - Sinisterra, Santiago; Camargo-Amado, Rubén; Triviño, Diego; Machuca Martínez, Fiderman (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The development of ceramic nanomaterials with self-cleaning properties is an important field of research since they can be used in different sectors such as the textile, aerospace, automotive and biomedical protection elements. The objective of the work is to analyze and identify world trends in research, level of innovation, as well as emerging technologies in the development of TiO2/ ZnO nanoparticles with antibacterial and self-cleaning properties; based on the technological monitoring of patents and Scholarly works using bibliometric methods using Lens bibliometric analysis software. The stages of technological development were estimated through the logistic model using the Loglet Lab4 software and the Yoon parameters, the Technological Maturity Rate (TMR), the potential patents to appear (EPP), the remaining lifetime (ERL) were calculated. four indicators were used: Granted patents (i1), patent applications (i2), scholarly Works (i3) and human capital (i4). The technological trend of patents for the first period focused on the development of catalysis processes, while in period II on technology for the manufacture of cosmetics and disinfectants. In period III, nanotechnology applied in cosmetics and disinfection processes appeared, finally, in period IV a trend towards disinfection and coating processes was observed, as well as the number of patent applications for this period. This technology of self-cleaning surfaces registered an average maturity rate of 72.3%, which is in a stage of maturity, being a technology classified as "leading technology" with the possibility of investment in the development of new products and processes.